Dry micro-electro-discharge machining of carbon-nanotube forests using sulphur-hexafluoride - Saleh, Tanveer; Dahmardeh, Masoud; Nojeh, Alireza; Takahata, Kenichi (Elsevier Limited, 2013)
The effect of using sulphur hexafluoride (SF6), a high-dielectric-strength gas, for dry micro-electro-discharge machining (μEDM) of carbon-nanotube (CNT) forests is investigated. It is found that SF6 enables μEDM of CNTs without O2, which is known to be essential for CNT machining in N2. The process in the SF6 ambient at a discharge voltage of 25 V is found to lead to a smaller discharge gap, i.e., tighter tolerance as well as higher machining quality compared with the N2 case at the same voltage. The N2 environment produces smaller discharge gap when 10 V is used; however, both the quality and rate of machining are somewhat lower in this case. The mixture with 20% O2 in SF6 is revealed to be an optimum condition for machining tolerance and quality. CNT forests are used as the cathode in the process, as opposed to conventional μEDM where the workpiece forms the anode. This configuration in the SF6–O2 mixture is observed to generate higher discharge currents at low voltages, presumably due to effective field-emission by the CNTs, leading to finer and cleaner machining. Energy-dispersive X-ray analysis reveals that the optimal conditions result in less contamination by the electrode element on the processed forest surfaces.